Time and Space in Digital Game Storytelling. (24th November 2010) - Wei, Huaxin; Bizzocchi, Jim; Calvert, Tom
Abstract : The design and representation of time and space are important in any narrative form. Not surprisingly there is an extensive literature on specific considerations of space or time in game design. However, there is less attention to more systematic analyses that examine both of these key factors—including their dynamic interrelationship within game storytelling. This paper adapts critical frameworks of narrative space and narrative time drawn from other media and demonstrates their application in the understanding of game narratives. In order to do this we incorporate fundamental concepts from the field of game studies to build a game-specific framework for analyzing the design of narrative time and narrative space. The paper applies this framework against a case analysis in order to demonstrate its operation and utility. This process grounds the understanding of game narrative space and narrative time in broader traditions of narrative discourse and analysis.